2018
DOI: 10.1016/j.ptsp.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Early anterior knee pain in male adolescent basketball players is related to body height and abnormal knee morphology

Abstract: Knee pain prevalence in adolescent basketball players was not related to differences between sides but was higher in tall players. Knee pain was accompanied by morphological abnormalities detected with ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…These results are consistent with previous findings on male runners, where the dynamic Q-angle did not change with pain [ 44 ], but there has been no similar study on female runners. We did not find height to be a predictor of pain score, which disagrees with the results of a previous study on adolescent male basketball players [ 57 ] that showed that the knees of taller subjects must endure more mechanical stress than those of shorter subjects due to the increased torque acting on the knees’ structures [ 57 ]. However, this idea did not seem to apply to our sample of female Asian soccer players.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with previous findings on male runners, where the dynamic Q-angle did not change with pain [ 44 ], but there has been no similar study on female runners. We did not find height to be a predictor of pain score, which disagrees with the results of a previous study on adolescent male basketball players [ 57 ] that showed that the knees of taller subjects must endure more mechanical stress than those of shorter subjects due to the increased torque acting on the knees’ structures [ 57 ]. However, this idea did not seem to apply to our sample of female Asian soccer players.…”
Section: Discussioncontrasting
confidence: 99%
“…After screening the full text, 30 articles were excluded. The reasons for exclusion were: the articles did not meet the requirements for a prospective cohort or an RCT (n = 15) [20][21][22]28,30,31,[34][35][36][39][40][41][42][43]48] , the articles were not specifically about youth basketball players (n = 13) [21,[23][24][25][26]29,32,37,38,[44][45][46][47] ,or there were no outcome measures (n = 2). [27,33] Figure 1 presents the search procedure.…”
Section: Search Strategiesmentioning
confidence: 99%
“…Regular sports activity improves skeletal muscle function and cardiovascular health, as well as prevents and reverses obesity, reduces anxiety and depression, and improves selfconfidence and cognitive function [1,2]. Basketball involves frequent jumping, accelerating, decelerating, turning, and pivoting [3].…”
Section: Introductionmentioning
confidence: 99%